A exposição do sagrado no museu - Roque, Maria Isabel (2015)
The sacred is interdict, so its exposure in the secular space of the museum seems to be contradictory. Christianity, however, creates a precedent in the context of religions, to restrict the interdiction, allowing the sacred objects, when disaffected, to be transferred to museological functions. The history of Portuguese museology is made largely from ecclesiastical initiatives and using sacred art objects. However, in the first museums, religion object was taken as an art object. Only later, museums became aware of the importance of data such as function, meaning and symbol. In order of this, the current museography designs strategies that enhance the content of the sacred in the religious heritage.